(untitled) (Foro de Educacion, 2024)
The present article analyzes a wide range of artistic manifestations related to non-standard sexualities represented in queer and feminist theoretical approaches included in well known texts. Three main branches of research, among many others, are suggested. These have been developed by various plastic artists who, in recent years, have proposed, with or without success, alternative ways to understand sexuality beyond the strict binary organization contained in the (antagonistic) images of man/woman, heterosexual/homosexual, and masculine/feminine.